Delivery of hepato-pancreato-biliary surgery during the COVID-19 pandemic: an European-African Hepato-Pancreato-Biliary Association (E-AHPBA) cross-sectional survey. Issue 8 (August 2020) - Balakrishnan, Anita; Lesurtel, Mickael; Siriwardena, Ajith K.; Heinrich, Stefan; Serrablo, Alejandro; Besselink, Marc G.H.; Erkan, Mert; Andersson, Bodil; Polak, Wojciech G.; Laurenzi, Andrea; Olde Damink, Stefan W.M.; Berrevoet, Frederik; et al.
Abstract: Background: The extent of the COVID-19 pandemic and the resulting response has varied globally. The European and African Hepato-Pancreato-Biliary Association (E-AHPBA), the premier representative body for practicing HPB surgeons in Europe and Africa, conducted this survey to assess the impact of COVID-19 on HPB surgery. Methods: An online survey was disseminated to all E-AHPBA members to assess the effects of the pandemic on unit capacity, management of HPB cancers, use of COVID-19 screening and other aspects of service delivery. Results: Overall, 145 (25%) members responded. Most units, particularly in COVID-high countries (>100, 000 cases) reported insufficient critical care capacity and reduced HPB operating sessions compared to COVID-low countries. Delayed access to cancer surgery necessitated alternatives including increased neoadjuvant chemotherapy for pancreatic cancer and colorectal liver metastases, and locoregional treatments for hepatocellular carcinoma. Other aspects of service delivery including COVID-19 screening and personal protective equipment varied between units and countries. Conclusion: This study demonstrates that the COVID-19 pandemic has had a profound adverse impact on the delivery of HPB cancer care across the continents of Europe and Africa. The findings illustrate the need for safe resumption of cancer surgery in a "new" normal world with screening of patients and staff for COVID-19.